The EU’s ‘Value-based Trade Agenda’: Trade and Sustainable Development Chapters in CETA - Lichtenberger, Andreas; Price, Kenya; Spinner, Marcel (Momentum Quarterly, 2018)
The adoption of CETA (currently under provisional enforcement) represents a new form of trade liberalisation that goes beyond the stalemates of WTO trade negotiations. Shaped by the ‘Trade for All’ agenda of the European Commission, trade policies are intended to be a key tool for meeting the UN Sustainable Development Goals. This paper aims to clarify the integration of sustainable development (SD) in CETA by analysing its Trade and Sustainable Development Chapters (TSD). Using a critical realist approach, structural and discursive selectivities are applied to shed light on the implementation of sustainability in CETA, drawing on examples from the agricultural sector. This study’s findings report protective potentials as the inclusion of the precautionary principle, a right to regulate and dispute settlements including civil society and independent experts; despite being framed as a ‘comprehensive set of binding provisions’, regulations regarding SD remain indeterminate and lack concretisation and clear sanctions in case legislations are not met.